2016
DOI: 10.1038/srep34932
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Reverse Dipper Blood Pressure Pattern in Chronic Kidney Disease Patients not Undergoing Dialysis: Prospective Cohort Study

Abstract: The “reverse dipping” blood pressure (BP) pattern has been studied among the general population and in individuals suffering from hypertension. However, the prognosis of this pattern in chronic kidney disease (CKD) patients is not known. We monitored BP throughout the day and followed health outcomes in 588 CKD patients admitted to our hospital. Time to all-cause mortality, cardiovascular mortality, renal events and cardiovascular events was recorded. Multivariate-adjusted Cox regression analyses were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The strong relationship between RD and nondipping status with increased urinary protein excretion has been recently confirmed by Wang and colleagues in 588 Chinese patients (67% with chronic glomerulonephritis). Proteinuria in reverse dippers was 66% higher than in dippers and approximately four‐fold greater than in extreme dippers.…”
Section: Search Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…The strong relationship between RD and nondipping status with increased urinary protein excretion has been recently confirmed by Wang and colleagues in 588 Chinese patients (67% with chronic glomerulonephritis). Proteinuria in reverse dippers was 66% higher than in dippers and approximately four‐fold greater than in extreme dippers.…”
Section: Search Methodsmentioning
confidence: 68%
“…In the setting of CKD, two studies consisting of 1024 individuals evaluated the risk of end‐stage renal disease and nonfatal/fatal cardiovascular events associated with RD. Both reports consistently documented that patients with RD had an increased risk of renal death and cardiovascular events compared with patients with preserved circadian BP rhythm, independently of 24‐hour systolic BP levels …”
Section: Search Methodsmentioning
confidence: 82%
“…29 Also, the strong relationship between increased urinary protein excretion and the RD and ND pattern is among the recently discussed topics. 30,31 When all these data are evaluated, it is clear that the RD and ND pattern is associated with an increased risk of CV disease. Although interest in sleep disorders has increased in recent years, the diagnosis and treatment of these patients is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides reverse dipping has also been shown to be associated with early carotid plaque formation in hypertensives (12 ). Chang Wang et al showed prognostic value of reverse dipper pattern in chronic kidney disease patients in their studies (13 ). However there was limited data involving cardiovascular effects of reverse dipper pattern.…”
Section: Discussionmentioning
confidence: 99%